The role of social cues in the deployment of spatial attention: head-body relationships automatically activate directional spatial codes in a Simon task - Pomianowska, Iwona; Germeys, Filip; Verfaillie, Karl; Newell, Fiona N. (Frontiers in Integrative Neuroscience, 2012)
The role of body orientation in the orienting and allocation of social attention was examined using an adapted Simon paradigm. Participants categorized the facial expression of forward facing, computer-generated human figures by pressing one of two response keys, each located left or right of the observers' body midline, while the orientation of the stimulus figure's body (trunk, arms, and legs), which was the task-irrelevant feature of interest, was manipulated (oriented toward the left or right visual hemifield) with respect to the spatial location of the required response. We found that when the orientation of the body was compatible with the required response location, responses were slower relative to when body orientation was incompatible with the response location. In line with a model put forward by Hietanen (1999), this reverse compatibility effect suggests that body orientation is automatically processed into a directional spatial code, but that this code is based on an integration of head and body orientation within an allocentric-based frame of reference. Moreover, we argue that this code may be derived from the motion information implied in the image of a figure when head and body orientation are incongruent. Our results have implications for understanding the nature of the information that affects the allocation of attention for social orienting.